Association of Toll‐like 4 receptor gene polymorphism (rs4986790, rs4986791) with the risk of urinary tract infection: A systematic review and meta‐analysis. Issue 3 (21st November 2019) - Huang, Wen‐Lin; Xu, Yong; Wan, Shaw‐Pong
Abstract: Recently published studies had shown that there may be a potential link between the Single nucleotide polymorphism (SNP) of Toll‐like receptor‐4 (TLR4), and the risk of urinary tract infection (UTI); however, no consensus was reached. To further understand the relationship between TLR SNPs and urinary tract infections, we searched for related studies published in PubMed, EMBASE, and Web of Science before October 30, 2018, for further systematic review and meta‐analysis. Our study accrued 10 case‐control studies, which included 1476 urinary tract infection patients and 1449 healthy controls in TLR4(rs4986790, rs4986791). R3.4.2 and Stata 15.0 software were used for the analysis. In general, there was no statistically significant association between rs4986790 and urinary tract infection in the four genetic models. However, in the subgroup analysis, the Asian population showed significantly difference in the allelic model (G vs A: OR = 1.88 [95% CI:1.42‐2.49], P = .03). In addition, there were also significant differences in the dominant model (GG + AG vs AA OR = 1.97 [95% CI:1.46‐2.66], P = .01). Due to the small number of available literatures, no meaningful conclusion can be drawn regarding the relationship between TLR4 (rs4986791) and the risk of urinary tract infections in general. Nevertheless, our meta‐analysis shows that in Asian populations, TLR4 (rs4986790) may be associated with risk of urinary tract infection.